2014
DOI: 10.1016/j.schres.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and pattern of childhood symptom onset reported by first episode schizophrenia and clinical high risk youth

Abstract: Background Psychosis prevention and early intervention efforts in schizophrenia have focused increasingly on sub-threshold psychotic symptoms in adolescents and young adults. Although many youth report symptom onset prior to adolescence, the childhood incidence of prodromal-level symptoms in those with schizophrenia or related psychoses is largely unknown. Methods This study reports on the retrospective recall of prodromal-level symptoms from 40 participants in a first-episode of schizophrenia (FES) and 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Another limitation relates to the assessment of CHR in pediatric populations. Although childhood onset of prodromal symptoms is not rare (Woodberry et al, 2014), identification of CHR in pediatric populations is less reliable than in adults (Schultze-Lutter et al, 2015). Furthermore, the predictive validity of the SIPS, particularly in children under age 10 years, is not established.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation relates to the assessment of CHR in pediatric populations. Although childhood onset of prodromal symptoms is not rare (Woodberry et al, 2014), identification of CHR in pediatric populations is less reliable than in adults (Schultze-Lutter et al, 2015). Furthermore, the predictive validity of the SIPS, particularly in children under age 10 years, is not established.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in patients with a first-episode of psychosis reported that attenuated psychotic symptoms occurred on average 3.9 years before admission to a hospital for a psychotic episode (Schultze-Lutter et al, 2010). A recent prospective study (Woodberry et al, 2014) reported that in a sample of 39 people at CHR for psychosis, for 23% the onset of SOPS unusual thought content, suspiciousness or perceptual abnormalities occurred in childhood, for 38.5% in adolescence, and for 38.5% in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…9, 11 Often earliest to emerge are heterogeneous symptoms: attention problems, depression, anxiety, avolition, social difficulties, disorganization, and sleep disturbances, so-called “non-specific symptoms”. 9, 10, 12, 13 More specific psychotic-like symptoms may emerge closer to the onset of acute psychosis.…”
Section: Phenomenology and Identification Of Emerging Psychosismentioning
confidence: 99%
“…21, 22 They have high rates of cognitive complaints (e.g., concentration or memory problems) and negative symptoms (e.g., low motivation or social anhedonia). 11, 23 Longstanding or worsening functional difficulties are also common. 24, 25 The vast majority has had previous treatment with psychotherapy or psychotropic medications.…”
Section: Phenomenology and Identification Of Emerging Psychosismentioning
confidence: 99%
See 1 more Smart Citation